Are all types of real transaction management equal in the eyes of bank lenders? - Chen, Po‐Chang; Moser, William J.; Narayanamoorthy, Gans (Journal of business finance & accounting, 2023)
This study examines whether bank lenders react differently to various types of real transaction management (RTM) by borrowing firms. Drawing upon the differential cash and cash flow effects of alternative forms of RTM, we predict and find that banks provide more favorable loan terms, that is, lower interest spread and reduced likelihood of required collateral, for firms reporting more discretionary reductions in research and development (R&D) expenditures. In contrast, lending banks respond unfavorably to borrowers’ engagement in RTM through aggressive sales discounts and overproduction of inventories. Additional analysis reveals that the favorable effect of discretionary R&D reductions on loan pricing is greater (smaller) for borrowing firms with a prior relationship with the bank or with a lower level of cash holdings (loans with longer maturity). Overall, our findings suggest that banks, with their unique payoff functions and monitoring incentives, do not view all forms of RTM negatively.